PENGARUH PERMAINAN DRAMA MINI TERHADAP KEMAMPUAN SOSIAL ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK NEGERI PEMBINA 01 SUTERA - Andella, Liza; Utoyo, Setiyo; Mayar, Farida; Yeni, Indra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study employed a quantitative approach using a quasi-experimental design. The research involved children at Taman Kanak-kanak Negeri Pembina 01 Sutera. The sample was selected using a purposive sampling technique, with class B2 as the experimental group and class B3 as the control group, each consisting of 11 children. Data were collected using a test consisting of six statement items. The data analysis technique used in this study was a comparison of the differences between two mean scores, analyzed using a t-test. Data processing was conducted using SPSS version 26 for Windows.Based on the post-test hypothesis testing, the significance value (2-tailed) was 0.115 < 0.005. Therefore, it indicates that there is a significant difference between the mini drama game and the teacher’s instructional treatment in relation to children’s social skills. It can be concluded that the mini drama game has an effect on children’s social skills.